Pengaruh konflik peran, ambiguitas peran dan stres kerja terhadap kinerja karyawan - Ismi Rija Nur; Tetra Hidayati; Siti Maria (JURNAL MANAJEMEN, 2016)
The purpose of this research is to know how big the influence of Role Conflict, Role Ambiguity and Job Stress on the Employee’s Performance at PT . Midi Utama  Indonesia Tbk Branch Samarinda . The sample on this research is consist of 40 respondents which are chosen from the method of Accidental Sampling . The analyst means that is used in this research is the multiplied linear regression with the help of IBM program Statistical Product and Service Solution ( SPSS ) 22 For Windows. The results of this research shows that partially of the hypothesis with the t- test where X1 = -2.283 ; X2 = -4.290 ; X3 = 3.426 . The variable negative value of Role Conflict, Role Ambiguity on the Employee’s Performance and positve value Stress Of Work on the Employee’s Performance has a strong relationship.Keyword: Role Conflict , Role Ambiguity , Work Stress and Employee Performance.